Linear Address Spaces. - KAMP, POUL-HENNING (Communications of the ACM, 2022)
The article discusses various aspects of computer-related linear physical and virtual addresses, and it mentions Cambridge University’s CHERI computer architecture platform and the computer memory-based difficulties that are associated with translating from linear virtual to linear physical addresses. The ARM and x64 types of central processing units (CPUs) are examined, along with object-oriented computing and the Rational R1000/s400 computer.